2013
DOI: 10.1155/2013/761852
|View full text |Cite
|
Sign up to set email alerts
|

[6]-Gingerol Prevents Disassembly of Cell Junctions and Activities of MMPs in Invasive Human Pancreas Cancer Cells through ERK/NF-κB/Snail Signal Transduction Pathway

Abstract: To study the effects of [6]-gingerol, a ginger phytochemical, on tight junction (TJ) molecules, we investigated TJ tightening and signal transduction pathways in human pancreatic duct cell-derived cancer cell line PANC-1. The following methods were utilized: MTT assay to determine cytotoxicity; zymography to examine matrix metalloproteinase (MMP) activities; transepithelial electrical resistance (TER) and paracellular flux for TJ measurement; RT-PCR and immunoblotting for proteins related to TJ and invasion; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…Similarly, Weng et al showed that 6-shogaol and 6-gingerol exerted antiinvasive activity against hepatoma cells through regulation of MMP-9 and TIMP-1 in a dose dependent manner [17]. Kim and Kim also suggested that 6-gingerol inhibited the invasiveness of pancreatic cancer (PANC-1) cells by decreasing the levels of protease, MMP-2, and MMP-9 [34]. All these reports supported our findings that the natural compounds such as 6-gingerol, present in Z. officinale rhizomes, play important anti-MMPs role.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Weng et al showed that 6-shogaol and 6-gingerol exerted antiinvasive activity against hepatoma cells through regulation of MMP-9 and TIMP-1 in a dose dependent manner [17]. Kim and Kim also suggested that 6-gingerol inhibited the invasiveness of pancreatic cancer (PANC-1) cells by decreasing the levels of protease, MMP-2, and MMP-9 [34]. All these reports supported our findings that the natural compounds such as 6-gingerol, present in Z. officinale rhizomes, play important anti-MMPs role.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports demonstrated that [6]-gingerol induce apoptosis by suppressing inducible nitric oxide synthase (iNOS), tumor necrosis factor alpha (TNF-α) expression, IkappaB alpha (IκBα) phosphorylation, nuclear factor kappa B (NF-κB) nuclear translocation, and ERK1/2/JNK/AP-1 pathway and also by activating mitochondria pathway [13,14]. Zerumbone inhibited the NF-kappaB-dependent reporter gene (TNF, TNFR1, TRADD, TRAF2, NIK, and IKK), suppression of antiapoptotic and metastatic gene expression (Akt and FOXO1 activation), upregulation of apoptosis, and downregulation of invasion (MMP9, VEGF, interleukin IL-6/8) in human breast and GBM 8401 cells [15,16]. It has been demonstrated that ganoderic acids (mushroom products) suppress growth by downregulating the expression of various NF-κB-regulated genes including genes involved in cell proliferation (c-Myc and cyclin D1), anti-apoptosis (Bcl-2), invasion (MMP-9), and angiogenesis [17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…Whereas Tangeretin is a methoxyflavone from citrus fruits that effectively reduced the tumor growth of human breast and promyelocytic leukemia cells by suppressing tumor cell proliferation markers (PCNA, COX-2, and Ki-67), matrix metalloproteinase (MMP-2/9), vascular endothelial growth factor, and extracellular-signal-regulated kinases 1/2 (ERK1/2) phosphorylation and also by arresting the cancer cell division at the G1/S phase via p53/p21 upregulation [11,12]. [6]-Gingerol and Zerumbone (components of ginger) has been used to treat numerous types of disease of human colon and breast cells [13][14][15][16]. Recent reports demonstrated that [6]-gingerol induce apoptosis by suppressing inducible nitric oxide synthase (iNOS), tumor necrosis factor alpha (TNF-α) expression, IkappaB alpha (IκBα) phosphorylation, nuclear factor kappa B (NF-κB) nuclear translocation, and ERK1/2/JNK/AP-1 pathway and also by activating mitochondria pathway [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies show that dietary intake antioxidants and/or polyphenols have an inverse risk effect on several aerodigestive cancers by mitigating the increase in inflammation [2024]. Curcumin, a compound from turmeric, along with several other natural agents, silibinin, silymarin, quercetin, neem & nimbolide, gingerol, epigallatecatechin-3- gallate (EGCG), genistein and resveratrol, all have been heavily research in aerodigestive cancers as preventive agents, front line therapy and/or in combination with more traditional therapeutics agents in the clinic [6,2528,9,2933]. In this review we will focus on these compounds, their effects on inflammatory signaling pathways, effects on epigenetic regulators and discuss how these natural products (NPs) can enhance clinical treatments.…”
Section: Introductionmentioning
confidence: 99%